Poverty Analysis of Cassava Farmers in Wonogiri Regency, Indonesia - Arbianti Arbianti; Endang Siti Rahayu; Joko Sutrisno (Sosiohumaniora, 2023)
Poverty is a central issue in development programs in Indonesia. Most people still depend on agriculture for their livelihoods with relatively low productivity and business income, so poverty are common in rural areas. Most of the Wonogiri residents work in agriculture, where one of the superior products is cassava, the largest producer in Central Java. Poverty reduction in agriculture is a critical factor in reducing poverty in Indonesia. This study examined the poverty status and determinants affecting the poverty status of cassava farmers in Wonogiri Regency, Indonesia. Purposive sampling techniques were used in 120 cassava farmers in Wonogiri Regency. Primary data were obtained with the aid of well-structured questionnaires and interviews. The data were analyzed using Foster-Greer Thorbecke (FGT) index and logistic regression (logit). The result of Foster Greer-Thorbecke's (FGT) analysis showed that headcount index (P0) was 0,3417, poverty gap index (P1) was 0,2092, poverty severity index (P2) was 0,1280. The logistic regression (logit) showed that determinants of the poverty status of cassava farmers were education, land area, household size, and farming experience. There needs to be an increase in education, land area, farming experience, and reduce the number of family dependents with family planning government programs.